PELINDUNGAN HUKUM BAGI DOKTER SPESIALIS MATA DALAM PELAKSANAAN TELEMEDISIN DI INDONESIA - Debiana Dewi Sudradjat (Faculty of Law, Parahyangan Catholic University, 2025)
Indonesia, as a nation embracing the welfare state principle, seeks to guarantee equal access to health services through the utilization of telemedicine. The Ministry of Health has issued regulations aimed at maintaining the uniformity and reliability of digital healthcare services nationwide. Nevertheless, the implementation of telemedicine relies heavily on medical professionals, whose work must be supported by adequate legal protection. Using a doctrinal research method with an analytical approach, this study identifies significant shortcomings in the existing legal framework, particularly the absence of clear safeguards for ophthalmologists who may face potential legal liability arising from diagnostic inaccuracies related to patient imaging in telemedicine practices. The findings highlight the urgent need to establish a comprehensive legal framework that ensures the protection of medical professionals, especially ophthalmologists, while strengthening the sustainability and effectiveness of telemedicine delivery in Indonesia.